(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2014)
This paper is a study of rape in the national capital of India, and the focus is on the amendments of rape law aftermath 12 December 2012 crime. It questions at the safety and security issues of women in the metropolis of India, and it also discusses critically how laws amendments have been made aftermath this barbaric crime. Though this paper doesn’t set an inquiry yet it provides common criticism against the new amendments and it remains observational in nature, and sets a study. The temporal aspect revolves around the gang rape case of December 2012, but it also peeks in the past for the reference purpose only. The insensitive reactions from the political party leaders and religious leaders also find a space in the paper to show the general reaction of the society. The urban middle-class carefree attitude is reflected by an example of a popular reality show. But finally this paper advocates for lengthy prison sentences that have some behavior-altering deterrent value.